New Caledonia as the centre of origin of Parastephanellus Enderlein, with a phylogeny and description of the female of P. khogis Aguiar (Hymenoptera, Stephanidae) - Aguiar, Alexandre P.; Jennings, John T. (Zootaxa, 2007)
The female for Parastephanellus khogis Aguiar is described, expanding the knowledge of the family Stephanidae in New Caledonia, previously centered on four species all known from single specimens. We also provide additional localities for P. khogis and discuss the morphological variation among the New Caledonian taxa, which seems to be morphologically conservative. A preliminary cladistic analysis including all stephanid species from New Caledonia and 63 species from other biogeographic regions suggests the origin of the genus Parastephanellus Enderlein in New Caledonia (lineage of P. delicatus Aguiar and P. mouensis Aguiar), and a recolonisation with taxa related to a possibly Australian lineage (P. khogis and P. sarramea Jennings).